Impact of meal fatty acid composition on postprandial lipaemia, vascular function and blood pressure in postmenopausal women. Issue 2 (16th March 2018) - Rathnayake, Kumari M.; Weech, Michelle; Jackson, Kim G.; Lovegrove, Julie A.
Abstract: CVD are the leading cause of death in women globally, with ageing associated with progressive endothelial dysfunction and increased CVD risk. Natural menopause is characterised by raised non-fasting TAG concentrations and impairment of vascular function compared with premenopausal women. However, the mechanisms underlying the increased CVD risk after women have transitioned through the menopause are unclear. Dietary fat is an important modifiable risk factor relating to both postprandial lipaemia and vascular reactivity. Meals rich in SFA and MUFA are often associated with greater postprandial TAG responses compared with those containing n -6 PUFA, but studies comparing their effects on vascular function during the postprandial phase are limited, particularly in postmenopausal women. The present review aimed to evaluate the acute effects of test meals rich in SFA, MUFA and n -6 PUFA on postprandial lipaemia, vascular reactivity and other CVD risk factors in postmenopausal women. The systematic search of the literature identified 778 publications. The impact of fat-rich meals on postprandial lipaemia was reported in seven relevant studies, of which meal fat composition was compared in one study described in three papers. An additional study determined the impact of a high-fat meal on vascular reactivity. Although moderately consistent evidence suggests detrimental effects of high-fat meals on postprandial lipaemia in postmenopausal (than premenopausal) women, there is insufficient evidence to establish the impact of meals of differing fat composition. Furthermore, there is no robust evidence to conclude the effect of meal fatty acids on vascular function or blood pressure. In conclusion, there is an urgent requirement for suitably powered robust randomised controlled trials to investigate the impact of meal fat composition on postprandial novel and established CVD risk markers in postmenopausal women, an understudied population at increased cardiometabolic risk.